Making Decisions Using Force Field Analysis - Seth Heinert; Sebastian Galindo-Gonzalez (EDIS, 2016)
Should I adopt water conservation practices? Should I start a community garden? Should I stop using fertilizer on my lawn? These kinds of complex decisions are often difficult because many factors are at play, each with different degrees of importance. Conducting a force field analysis is a simple technique that can help an individual or groups more effectively make decisions and also more holistically consider key factors. Force field analysis allows you to make decisions based on the idea that a point of equilibrium exists within any system. Any proposed change causes a shift in this equilibrium. This 4-page fact sheet describes how to conduct a force field analysis, provides a relevant example, and suggests possible applications. Written by Seth Heinert and Sebastian Galindo-Gonzalez, and published by the Agricultural Education and Communication Department, August 2015.